Meaning of Love in the Novel "Ziarah" by Iwan Simatupang - Mayske Rinny Liando; Intama Jemy Polii; Viktory Nicodemus Joufree Rotty; Maya Lidya Maria Rotty (International Journal on Integrated Education, 2022)
Literature is an expression of the problems of life, philosophy and psychology, literature is spiritual wealth. Writers can be said to be experts in psychology and philosophy who express problems in life, psychology and philosophy. not by academic technique but through literary writing. The focus in this research is on the content of the novel, especially about the meaning of love in the Ziarah Novel by Iwan Simatupang according to the study of existential philosophy according to Soren Kierkegaard, namely the aesthetic stage, ethical stage, and religious stage. The problems raised in this study are guided by qualitative descriptive research methods. This method is an assessment that is not designed with statistical procedures. The purpose of this study is to describe what conditions exist in a context. Qualitative method is a research procedure that produces descriptive data in the form of written or spoken words from observable behavior. The results of the study thatThe meaning of love at the Aesthetic stage of Soren Kierkegaard's Existential philosophy in Iwan Simatupang's Ziarah novel is Pleasure and Distress, The meaning of love at the Ethical stage of Soren Kierkegaard's Existential philosophy in Iwan Simatupang's Ziarah novel is Good and Evil and the Meaning of Love at the Religious stage of Soren Kierkegaard's Existential philosophy in I wan Simatupang's pilgrimage novel is Grace, Faith and Sin.